2018
DOI: 10.3892/ol.2018.9730
|View full text |Cite
|
Sign up to set email alerts
|

Paeonol‑mediated apoptosis of hepatocellular carcinoma cells by NF‑κB pathway

Abstract: The aim of the study was to investigate the effect of paeonol on the apoptosis of hepatocellular carcinoma cells and to explore the possible mechanism of its effect. During the experiment, the human hepatoma (Huh7) cell line was cultured and treated with different concentrations of paeonol. A 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay was used to detect the effects of paeonol at different concentrations on the proliferation of Huh7 cells after 24 h, and the optimal concentration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
2
7
0
Order By: Relevance
“…Induction of apoptosis is one of the most important and direct pathways that controls and eliminates cancer proliferation (11,34). The FcM results of the present study demonstrated that paeonol dose-and time-dependently induced cell apoptosis, which was in line with previous studies of cRc cells (29) and other cancer cells (11,31).…”
Section: Discussionsupporting
confidence: 92%
“…Induction of apoptosis is one of the most important and direct pathways that controls and eliminates cancer proliferation (11,34). The FcM results of the present study demonstrated that paeonol dose-and time-dependently induced cell apoptosis, which was in line with previous studies of cRc cells (29) and other cancer cells (11,31).…”
Section: Discussionsupporting
confidence: 92%
“…The results of the present study showed that paeonol significantly enhanced apoptosis and increased the sub-G1 fraction of HCC cells, a finding consistent with that of previous studies ( 11 , 26 ). The proliferation of HCC cells was also suppressed by paeonol, which confirmed a previous report that paeonol might induce HCC cell apoptosis via the NF-κB pathway ( 11 ). However, the effect of paeonol on survivin in HCC has not been previously examined.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, paeonol has been reported to exert antitumor activities in ovarian cancer cells ( 7 ), prostate cancer cells ( 8 ), breast cancer cells ( 9 ), and gastric cancer cells ( 10 ). Previous studies have shown that paeonol induces apoptosis of hepatoma cells via the nuclear factor kappa-B (NF-κB) pathway ( 11 ). Paeonol has also been shown to decrease oxidative injury and improve immunity in rats with HCC ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Paeonol, a phenolic compound isolated from Paeonia suffruticosa, has been shown to have a wide range of pharmacological activities including antioxidant and anti-inflammatory properties [9] that may be beneficial in various diseases such as diabetes [10], cancer [11], gastric ulcer [12], liver fibrosis [13], and myocardial infarction [14]. Paeonol has been proven to have a protection against antineoplastic-induced toxicities such as cisplatin-induced nephrotoxicity [15] and epirubicininduced cardiac toxicity [16]; however, to date, this role has not been investigated in MTX-induced cardiac toxicity.…”
Section: Introductionmentioning
confidence: 99%